Peran Place Attachment sebagai Mediator Pengaruh Place Image terhadap Affective Resident Commitment Kota Palangka Raya - Haris Fadillah; Yadi Ernawadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the role of place attachment as a mediator of the influence of place image on affective resident commitment in Palangka Raya City. The research method used was a survey with a quantitative approach, utilizing primary data collected through questionnaires from 228 respondents from Palangka Raya City who were at least 17 years old, employed, and had resided in the city for at least five years. The sampling technique used convenience sampling, while data analysis was conducted using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method using the SmartPLS version 3.0 application. The results showed that physical appearance and ambient, social environment, and traditional market facilities had a positive and significant effect on place attachment, while leisure had no significant effect. Furthermore, place attachment was proven to have a positive and significant effect on affective resident commitment and acted as a mediator of the influence of physical appearance and ambient, social environment, and traditional market facilities on affective resident commitment. While the influence of leisure was not mediated by place attachment. In conclusion, strengthening the city's place image through the physical environment, social environment, and traditional market facilities can increase the affective resident commitment of the Palangka Raya community through increased place attachment. This can serve as a basis for formulating city development policies oriented toward residents' emotional attachment and affective commitment. Keywords: Place Image, Place Attachment, Affective Resident Commitment, City Marketing